Botulinum neurotoxin serotype D – A potential treatment alternative for BoNT/A and B non-responding patients. Issue 6 (June 2019) - Kutschenko, Anna; Weisemann, Jasmin; Kollewe, Katja; Fiedler, Thiemo; Alvermann, Sascha; Böselt, Sebastian; Escher, Claus; Garde, Niklas; Gingele, Stefan; Kaehler, Stefan-Benno; Karatschai, Ralf; Krüger, Tillmann H.C.; et al.
Highlights: The murine ex vivo potency of BoNT/D is 3.7 times lower compared to BoNT/A. 110-fold higher protein dosage of BoNT/D achieved the same clinical effect as incobotulinumtoxinA. BoNT/D constitutes a potential treatment alternative for BoNT/A & B non-responder. Abstract: Objectives: Botulinum neurotoxin serotypes A and B (BoNT/A & B) are highly effective medicines to treat hyperactive cholinergic neurons. Due to neutralizing antibody formation, some patients may become non-responders. In these cases, the serotypes BoNT/C-G might become treatment alternatives. BoNT/D is genetically least related to BoNT/A & B and thereby circumventing neutralisation in A/B non-responders. We produced BoNT/D and compared its pharmacology with BoNT/A ex vivo in mice tissue and in vivo in human volunteers. Methods: BoNT/D was expressed recombinantly in E. coli, isolated by chromatography and its ex vivo potency was determined at mouse phrenic nerve hemidiaphragm preparations. Different doses of BoNT/D or incobotulinumtoxinA were injected into the extensor digitorum brevis (EDB) muscles (n = 30) of human volunteers. Their compound muscle action potentials were measured 11 times by electroneurography within 220 days. Results: Despite a 3.7-fold lower ex vivo potency in mice, a 110-fold higher dosage of BoNT/D achieved the same clinical effect as incobotulinumtoxinA while showing a 50% shortened duration of action. Conclusions: BoNT/D blocks dose-dependently acetylcholine release in human motoneurons upon intramuscular administration, but its potency and duration of action is inferior to approved BoNT/A based drugs. Significance: BoNT/D constitutes a potential treatment alternative for BoNT/A & B non-responders.